PENGARUH PENDAPATAN ASLI DAERAH. DANA PERIMBANGAN, SIZE PEMERINTAH DAERAH, DAN TINGKAT KEMISKINAN TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Helen Andaresta (2021)
This study aims to test and prove the relationship between local government financial performance and local revenue, balance funds, local government size , and poverty levels. This study uses the Regency / City Government on the Island of Sumatera in 2019. Sampling was using the census sampling method, namely 154 samples in the Regency / City Government on the island of Sumatra. Hypothesis testing in this study is multiple linear regression with SPSS. The results of this study are that local revenue has an effect on the financial performance of local governments, the balance fund has a negative effect on the financial performance of local governments, SizeLocal government has no effect on local government financial performance, and poverty level has a negative effect on local government financial performance. The contribution in this study to local governments is to provide suggestions to continuously improve government financial performance, as well as for various researchers by adding variables not examined in this study, and using other measurements and other theories in the size variable of local government.